The Relationship Between Social Identity and Individual Involvement in the Community Toward a Sense of Community: My Day Indonesia at the Day6 Forever Young 2025 Jakarta Concert - Zakiyah Aulia Sabrina Hanifah Jauhary; Rifqi Farisan Akbar (International Journal of Marketing & Human Resource Research, 2026)
This research investigates the psychosocial dynamics within the My day Indonesia fan community of Day6 triggered by widespread dissatisfaction with the "Day6 Forever Young 2025" concert promoter, a phenomenon feared to undermine internal cohesion. The study aims to examine the correlations among Social Identity, Individual Involvement, and Sense of Community in this challenging situation. Using a quantitative approach, the study surveyed 100 respondents selected via probability sampling (Slovin’s formula, 10% error margin) from a population of 8,469 participants in the Jakarta concert. Parametric statistical testing revealed that both independent variables were significantly positively associated with the dependent variable. Specifically, Social Identity showed a strong correlation with Sense of Community (r = 0.725; p < 0.05), whereas Individual Involvement showed a moderate correlation (r = 0.515; p < 0.05). The simultaneous analysis further confirmed a significant collective relationship (r = 0.730; p < 0.05). These findings emphasize that in times of crisis, a strong sense of identity and active individual engagement are pivotal in preserving the bond and togetherness of the My Day Indonesia community.